Does Demographics Matter in Measuring Customer Satisfaction: Hypothetical Evidence from Indian Telecom Sector - Nishant Dabhade; Ankit Gupta (Universitas Trisakti, 2021)
Virtually all the sectors of economy such as finance, banking, hospitality and other businesses have grown up substantially in the past few years due to the growth of mobile service sector. From the inception of Reliance Jio in Madhya Pradesh, It has occupied a large number of customers in terms of no. of subscribers. This creates unrest among the telecom service operators operating in Madhya Pradesh. As the market moves forward, customer satisfaction becomes imperative for service firms to remain combative at marketplace. To study customer satisfaction, it is mandatory to study socio demographics of customers. Hence efforts have been made in this research paper to study the satisfaction level of customers from several demographic variables. This is a hypothetical research study in which primary data is collected from 500 active mobile users of Bhopal (MP), India. One way ANOVA and T-test were used to analyze the data through SPSS 21.0 software. Specific variables of American customer satisfaction index (ACSI) and European customer satisfaction index (ECSI) were being studied with different socio demographic variable of customers to move ahead in present research study. Significant difference was found in level of customer satisfaction with the age group and type of connection in telecom sector.